Individualized Learning System: The Efficiency of Tailored Learning - Zia, Fatima (Students' Supplement of Journal of Rawalpindi Medical College, 2024)
Learning systems had been developed to intricate the needs, objectively and subjectively for traversing of the knowledge. Where the world has become more diverse and demands are ever-increasing, stepping out of one fit model of learning in this open-world classroom of knowledge and experience has potentiated the overall efficacy of the learning. The history of research made to explore more about behavioral phenomena of human learning and excelling started with behaviorism theory, then Pavlov theory, and many more, and the progress that the human mind has come up to is best termed as adaptability. Such like that student coming up with strategies that are unique to their needs has proven to be more effective in active learning and better outcomes. Research made breakthroughs in the recognition of the role of motivation, learning strategies, and academic emotions in students’ learning and performance proving students who believed in themselves and more pronounced emotions using metacognitive learning strategies, resulting in better efficiency in academic performance.1 Coming with different pedagogical strategies that students can opt for according to their desires include spaced repetition, active recall, or designing a perfect study system using productivity tips like second brain, time blocking, promodoro technique, and many more. These different modalities needed to be studied by students according to need. Where active recall works by memorizing and retrieving information at best by using some clue points and making a connection with the term and information related to it. This can be done using flashcards, organized notes, and mnemonics. Spaced repetition is the formulation of a study schedule over a defined period with some strategic placement of academic goals over a period of hours or days. In this way, information can be stored and revised again and again which will increase long-term retention in memory and efficiently reduce the time needed for study. Research on spaced retrieval showed that repeated retrieval and spaced repetition enhance long-term retention.2 One study showed how students cope with fast-paced integrated medical school curricula where the better outcome was more with solidifying feedbacked testing in the form of retrieval format testing.3 When there is an abundance of information that needs to be dealt with, building the second brain can be helpful for medical students especially. This was introduced by Tiago Forte, where there is an external digital way of organizing and utilizing knowledge. The second brain is the scribbled page of whatsoever information you hold on about a topic so that when have to tackle with the knowledge it is not the blank page to start with. Along with this, time blocking the whole day may be useful for students who are more towards balance in daily life in concordance with studies or when more than one task is to be done in a day, such that the whole day is divided into blocks and each block assigned with specific goal or task which also improve the focus, stability, and swiftness in performing tasks. This overall improves the organization and convenience of time management, which is reinforced by the study that claims that this methodology allows students to manifest a study session for effective self-regulated and better academic performance by time management tactics.4 These learning systems do not overshadow the classic learning methodologies but reinforce the better management of input of the knowledge and ultimately the. They also include such designs that are proven to be useful when the classic models are integrated with advancing technologies and innovations like e-learning and m-learning.5 With the provision of better resources in this era of advancement there is more understanding of personalized proficient ways of learning as some students prefer books, some prefer pictorial and some prefer audiovisual learning. This has been made clear with different research on learners' approaches to reading and writing.6 Therefore, a student struggling to get best best-suited environment and opportunity must study his circumstances and focus on developing a personalized learning story of his own while balancing with ongoing challenges of settling with every changing minute needs. However, the subjective aspect of learning also needs to be realized and people associated with education must open chances for students to opt for more proficient ways to improve their ultimate efficiency in the long term.